A culture of knowledge production: testing and observation of Dutch children with learning and behavioural problems (1949–1985). - Bakker, Nelleke (Paedagogica Historica)
This article focuses on the role the Dutch school for children with “learning and behavioural problems” (LOM) has played in knowledge production about learning disabilities and in the development of academic study of special education between 1949 and 1985. LOM-schooling grew rapidly during these years and attracted relatively many experts. In the selection and admission of LOM-children they had to be distinguished from normal, mentally deficient, and “very difficult” children. Around 1970 experts shifted their focus from the distinction between LOM-children and the latter to the difference between LOM- and mildly mentally retarded children, which turned out to be too small in the end to justify a separate school. The LOM-school’s culture of knowledge production has stimulated both testing and the study of learning problems and their treatment. It functioned as a laboratory for the development of therapeutic treatment for learning disabilities. In particular, the systematic reflection on the practice of remedial teaching was relevant in the development of child science.